Lifetime prediction of biodegradable polymers. (August 2017) - Laycock, Bronwyn; Nikolić, Melissa; Colwell, John M.; Gauthier, Emilie; Halley, Peter; Bottle, Steven; George, Graeme
Abstract: The determination of the safe working life of polymer materials is important for their successful use in engineering, medicine and consumer-goods applications. An understanding of the physical and chemical changes to the structure of widely-used polymers such as the polyolefins, when exposed to aggressive environments, has provided a framework for controlling their ultimate service lifetime by either stabilising the polymer or chemically accelerating the degradation reactions. The recent focus on biodegradable polymers as replacements for more bio-inert materials such as the polyolefins in areas as diverse as packaging and as scaffolds for tissue engineering has highlighted the need for a review of the approaches to being able to predict the lifetime of these materials. In many studies the focus has not been on the embrittlement and fracture of the material (as it would be for a polyolefin) but rather the products of degradation, their toxicity and ultimate fate when in the environment, which may be the human body. These differences are primarily due to time-scale. Different approaches to the problem have arisen in biomedicine, such as the kinetic control of drug delivery by the bio-erosion of polymers, but the similarities in mechanism provide real prospects for the prediction of the safe service lifetime of a biodegradable polymer as a structural material. Common mechanistic themes that emerge include the diffusion-controlled process of water sorption and conditions for surface versus bulk degradation, the role of hydrolysis versus oxidative degradation in controlling the rate of polymer chain scission and strength loss and the specificity of enzyme-mediated reactions.